A Review of Bail and Pretrial Detention: U.S. Vs. Canadian Approaches to Fairness-2025 (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This review paper examines how bail and pretrial detention are applied in the United States and Canada, with attention to fairness, equality before the law, and the protection of individual rights. Bail decisions determine whether a person accused of a crime is released or held in custody while waiting for trial, even though they are legally presumed innocent. In the United States, the bail system relies solely on cash bail, meaning that many people remain in jail simply because they cannot afford to pay for their release. However, research shows that this approach affects low-income individuals and underrepresented groups, leading to unnecessary detention, loss of employment, family disruption, and a higher likelihood of conviction before trial. In contrast, Canada’s bail system is based on constitutional principles that emphasize the right to reasonable bail and the presumption of release. Canadian law requires that detention be justified by clear legal reasons, such as ensuring court attendance, protecting public safety, or maintaining public confidence in the justice system. Monetary bail plays a limited role, and courts are encouraged to use the least restrictive conditions possible. By comparing these two approaches, this paper highlights how legal frameworks shape real-world results in pretrial justice and discusses lessons that can inform ongoing reforms aimed at improving fairness and reducing unnecessary detention.